2023
DOI: 10.3389/fmed.2023.1094843
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcoidosis and HLA polymorphisms in a Czech population from Central Europe: focus on a relationship with clinical outcome and treatment

Abstract: BackgroundSarcoidosis is an immune-mediated systemic disease with unknown etiology affecting the lung predominantly. The clinical manifestation of sarcoidosis is rather diverse ranging from Löfgren’s syndrome to fibrotic disease. Also, it differs among patients with distinct geographical and ethnic origins, consistent with environmental and genetic factors’ role in its pathogenesis. Of those, the polymorphic genes of the HLA system have been previously implicated in sarcoidosis. Therefore, we have performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As a systemic illness with an unclear cause, sarcoidosis is genetically linked to several human white cell antigen (HLA) variations and genetic polymorphisms, mostly in the HLA region. [46,47] Studies have shown that HLA-DR3 is associated with a higher incidence of sarcoidosis, particularly in people with Lofgren's disease. [48][49][50][51] HLA-DR3 is surprisingly linked to a higher risk of CeD, according to studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a systemic illness with an unclear cause, sarcoidosis is genetically linked to several human white cell antigen (HLA) variations and genetic polymorphisms, mostly in the HLA region. [46,47] Studies have shown that HLA-DR3 is associated with a higher incidence of sarcoidosis, particularly in people with Lofgren's disease. [48][49][50][51] HLA-DR3 is surprisingly linked to a higher risk of CeD, according to studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other genes implicated include those influencing antigen processing and presentation, T-cell recruitment and activation, and granulomatous inflammation [55]. One specific HLA allele that increases the likelihood of sarcoidosis and radiographic progression among black families includes DQB1*0602 [58,59]. Butyrophilin-like 2 (BTNL2), located in the class II MHC region on chromosome 6, also confers an increased risk, along with other genetic variants, as detailed in Table 1 [60].…”
Section: Geneticsmentioning
confidence: 99%
“…The significance of these genetic imprints is important in the phenotypic classification of patients and in recognizing the predictive value of the prognosis of sarcoidosis. HLA-B7 [73] HLA-B8 [74] HLA-B*51 [75] HLA-C [58] HLA-DPA1/DPB1 [58] HLA-DPB1 (*0101) [61] HLA-DQA1*0301 [76] HLA-DQA1*0501 [77]: HLA-DQA1*0505 [58] HLA-DQB1*0201 [76] HLA-DQB1*0302 [58] HLA-DQB1*0503/4 [76] HLA-DQB1*0601 [78]:…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations